A Production Model for Deteriorating Inventory Items with Production Disruptions - Yong He; Ju He (Discrete Dynamics in Nature and Society)
Disruption management has recently become an active area of research. In this study, an extension is made to consider the fact that some products may deteriorate during storage. A production-inventory model for deteriorating items with production disruptions is developed. Then the optimal production and inventory plans are provided, so that the manufacturer can reduce the loss caused by disruptions. Finally, a numerical example is used to illustrate the model.